EXPERIENCE OF CINACALCET TREATMENT DURING PREGNANCY IN PRIMARY HYPERPARATHYROIDISM - Johari, Munir; Katiman, Elliyyin; Aziz, Hazwani (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Primary hyperparathyroidism (PHPT) in pregnancy is rare but associated with high maternal (68.6%) and foetal (80%) complications, including pre-eclampsia, miscarriage and intrauterine growth restriction. The risks are directly related to the severity of the disease and the serum calcium level. We describe two cases with differing clinical outcomes based on the timing of diagnosis and intervention. CASE A 30-year-old gravida 3, para 2, presented with maternal tachycardia at 27 weeks of gestation. On work-up, the patient was incidentally found to have hypercalcaemia. ECG showed a shortened QTc. Biochemically, her calcium was 2.99 mmol/L (Reference Value [RV]: 2.2–2.7 mmol/L), phosphate 0.7 mmol/L (RV: 0.8–1.45 mmol/L) and intact PTH level of 12.3 pmol/L (RV: 1.58–6.03), suggestive of parathyroid (PTH) dependent hypercalcaemia. Ultrasound showed an enlarged right parathyroid gland. Despite IV hydration, hypercalcaemia persisted, leading to cinacalcet initiation at 29 weeks. At 30 weeks, calcium was highest at 3.05 mmol/L. She was treated with subcutaneous salmon calcitonin (5 mg/kg/dose), which was given twice daily, and cinacalcet was titrated up to 75 mg/day. Her calcium decreased to 2.44 mmol/L after six doses of calcitonin. Eventually, she delivered vaginally at 38 weeks with no complications; the neonate weighed 2.58 kg. A 33-year-old primigravida developed hypertension at 22 weeks, progressing to preeclampsia with pulmonary oedema and blurred vision at 27 weeks, requiring emergency caesarean section. The neonate weighed 980 g; placental histology showed vascular malperfusion and retroplacental haematoma. Hypertension persisted post-delivery. Retrospectively, there was an unrecognised hypercalcaemia detected from 26 weeks gestation. Postpartum laboratory showed calcium 3.04 mmol/L, phosphate 0.67 mmol/L and intact PTH 20.3 pmol/L. Ultrasound and Tc-99m Sestamibi confirmed a left inferior parathyroid adenoma. She underwent a left parathyroidectomy, and she was immediately weaned off antihypertensives. CONCLUSION PHPT in pregnancy poses significant maternal and foetal risks. Medical therapy options are limited during pregnancy. Early recognition and tailored management are crucial to minimise maternal and foetal complications.